THE NETWORK EPES16–4 - Tuychiyev, Gulom; Jumakulov, Abdumannon (Евразийский журнал математической теории и компьютерных наук, 2023)
The article presents the EPES16–4 network with four round functions using the same algorithm for encryption and decryption.